2022
DOI: 10.1177/08980101221098102
|View full text |Cite
|
Sign up to set email alerts
|

Despite Symptom Severity, do Nursing Home Residents Experience Joy-of-Life? The Associations Between Joy-of-Life and Symptom Severity in Norwegian Nursing Home Residents

Abstract: Successful Completion Requirements to Receive a Certificate for 2.6 Contact HoursRequirements for successful completion includes: read the entire article, score 70% or better on posttest, complete the online evaluation form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In Norway, about 86% of long-term NH residents have extensive assistance needs; the mean residential stay is about one to two years, and annual mortality is about 40% (Norwegian Directorate of Health, 2020). Furthermore, symptom severity seems constantly high; in 2009 (Haugan, 2014d) and 2018 (Rinnan et al, 2022) symptom severity was reported respectively as: 57% and 54% fatigue, 43% and 52% constipation, 49% and 45% pain, 41% and 43% dyspnoea, 38% and 32% insomnia, 25% and 22% appetite loss, 18% and 20% nausea, 12% and 20% anxiety and 30% and 23% reported depressive symptoms. Nevertheless, a recent study demonstrates that despite these ailments, about 50% of residents in Norwegian NHs report a high joy-of-life (Rinnan et al, 2022).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In Norway, about 86% of long-term NH residents have extensive assistance needs; the mean residential stay is about one to two years, and annual mortality is about 40% (Norwegian Directorate of Health, 2020). Furthermore, symptom severity seems constantly high; in 2009 (Haugan, 2014d) and 2018 (Rinnan et al, 2022) symptom severity was reported respectively as: 57% and 54% fatigue, 43% and 52% constipation, 49% and 45% pain, 41% and 43% dyspnoea, 38% and 32% insomnia, 25% and 22% appetite loss, 18% and 20% nausea, 12% and 20% anxiety and 30% and 23% reported depressive symptoms. Nevertheless, a recent study demonstrates that despite these ailments, about 50% of residents in Norwegian NHs report a high joy-of-life (Rinnan et al, 2022).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Moving to a NH result from numerous losses, illnesses, disabilities, loss of functions and social relations and facing an end-of-life situation. Accordingly, the long-term NH population is characterised by a high incidence of chronic illness and functional impairments (Hoben et al, 2016), multiple simultaneous and complex diagnoses with a severe symptom burden, impaired functioning, various losses and fewer social relationships (Haugan, 2014b;Rinnan et al, 2022;Söderbacka et al, 2017). All of these increase an individual's vulnerability and distress.…”
Section: Loneliness Is More Detrimental To Nh Residents' Qol Than Anx...mentioning
confidence: 99%